Contributions of Catholic Universities in Yogyakarta to the Development of Community Transformative Dialogue - Mulyatno, Carolus Borromeus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2016)
The main tasks of the university are implementing learning, research, and community service. In a multicultural and multireligious Asia, the actualization of these tasks requires a dialogue with cultures, religions, and the poor. Today, the university must consider radical movements and fundamentalism that threaten harmony in the society. This paper is focused on opportunities that can be explored to realise the task of the Catholic universities in Yogyakarta in developing dialogue and harmony in Yogyakarta. This task might need a new and effective model of dialogue for a better living together in harmony. By applying a method of documental study and interviews, this study is focused on the exploration of challenges encountered by the Catholic universities in Yogyakarta in developing a community transformative dialogue. There are three main points. First, a description of the meaning of the community transformative dialogue. Second, an exploration of cultural potentials in Yogyakarta for developing community transformative dialogue. Third, a proposal for developing community transformative dialogue. These are three important results of this study. This transformative dialogue is a contextual and cultural dialogue that could be effective and appropriate for the multicultural and multireligious societies. In Yogyakarta, unity and harmony (keselarasan) are the core of the community that is necessary for the development of dialogue towards the well-being of the society. Catholic universities should encourage student activities in the campus and in the society as a praxis of continuous dialogue for a harmonious living together.